Proposta de ferramenta de gestão das bolsas de resíduos brasileiras com uso do Balanced Scorecard e Boston Consulting Group - Santolin, Rodolfo Cola (2014)
A great milestone for Brazil was the approval of the National Policy Solid Waste, on 2010 August 2nd, by Law number 12.305/10. The National Policy Solid Waste which introduced several mechanisms to minimize the negative impacts caused by consumers and manufacturers, defining managerial steps to minimize these impacts, with emphasis on reuse and recycling waste. For improving the percentage of reused and recycled products is the use of waste exchange as identifying markets for trading of waste by means of rapprochement between generators and interested in recycling and reuse. Waste exchange is an important tool for waste management in Brazil, but underutilized, because there are some obstacles in the management system that make it difficult to measure the importance of the mitigation process waste. This research is justified by the need to improvements in the management of waste exchange in order to increase the percentage of reuse and recycling of waste advertised, corroborating the National Policy Solid Waste, contributing to sustainable development. The objective of this research is to develop a framework of Balanced Scorecard (BSC) as proposed for use in the management of waste exchange of Brazilian in compliance with the principles and objectives of National Policy Solid Waste. The proposal to build a framework of BSC for management of waste exchange enables the development of a management tool based on four perspectives (financial, customer, internal processes and learning) for identifying obstacles management system and increase the use of waste exchange as a tool for National Policy Solid Waste. With respect to the research method, the paper presents a qualitative approach consisting of two phases: an xploratory literature and applied research. In conclusion the structure of BSC was developed and adapted for better operationalization of waste exchange in Brazilian customer service. The four perspectives are tuned to improve and enhance the information and services provided to users. The BSC developed proposed changes in the management structure of the waste exchange in order to enhance their use, increasing the volume of waste traded develop plans in conjunction with private sector (reduction, recycling and reuse) and changing it structure to operate with own resources, financially stable, according to the principles and objectives of National Policy Solid Waste.